2008
DOI: 10.18848/1833-1882/cgp/v03i04/52595
|View full text |Cite
|
Sign up to set email alerts
|

Culture Conflict Amongst Malaysian Children

Abstract: Culture is an essential part of conflict and conflict resolution. Culture is in our lives and relationships, giving us messages that shape our perceptions, attributions, judgments, and ideas of self and others. Though cultures are powerful, they are often unconscious, influencing conflict and attempts to resolve conflict in imperceptible ways. Two things that are essential to remember about culture: they are always changing, and they relate to the symbolic dimension of life. The symbolic dimension is the place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Administrators must address cultural complexity and promote cooperation between the parties. This is similar to the research of Hamzah et al [4] who studied multiculturalism in Malaysia and found that cultural differences affect conflict. The state's conflict resolution often uses socializing perception, background expression, and utilizes the ideas of one's own and others.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…Administrators must address cultural complexity and promote cooperation between the parties. This is similar to the research of Hamzah et al [4] who studied multiculturalism in Malaysia and found that cultural differences affect conflict. The state's conflict resolution often uses socializing perception, background expression, and utilizes the ideas of one's own and others.…”
Section: Introductionsupporting
confidence: 90%
“…(3) Accepting social change and knowing the method to design innovation to solve problems sustainably and adaptable. (4) Participating in projects creating awareness of cultural heritage that they have cultural and economic potentials, exchanging experience; transmitting knowledge between specialists, government officials, and local people. (5) Knowing to improve or develop new art and cultural heritage according to the need of the community and sustainability.…”
Section: Literature Reviewmentioning
confidence: 99%